Cardiac Rehabilitation for Patients With Coronary Artery Disease: A Practical Guide to Enhance Patient Outcomes Through Continuity of Care. Issue 11 (8th June 2017) - Giuliano, Catherine; Parmenter, Belinda J; Baker, Michael K; Mitchell, Braden L; Williams, Andrew D; Lyndon, Katie; Mair, Tarryn; Maiorana, Andrew; Smart, Neil A; Levinger, Itamar
Coronary artery disease (CAD) is a leading cause of disease burden worldwide. Referral to cardiac rehabilitation (CR) is a class I recommendation for all patients with CAD based on findings that participation can reduce cardiovascular and all-cause mortality, as well as improve functional capacity and quality of life. However, programme uptake remains low, systematic progression through the traditional CR phases is often lacking, and communication between health care providers is frequently suboptimal, resulting in fragmented care. Only 30% to 50% of eligible patients are typically referred to outpatient CR and fewer still complete the programme. In contemporary models of CR, patients are no longer treated by a single practitioner, but rather by an array of health professionals, across multiples specialities and health care settings. The risk of fragmented care in CR may be great, and a concerted approach is required to achieve continuity and optimise patient outcomes. 'Continuity of care' has been described as the delivery of services in a coherent, logical, and timely fashion and which entails 3 specific domains: informational, management, and relational continuity. This is examined in the context of CR.